Retribution versus Rehabilitation for Children within Insurgency: Public Attitudes Toward ISIS-Affiliated Youth in Mosul, Iraq - Mironova, Vera (Terrorism and political violence, 2025)
In the aftermath of insurgent violence, how do people view the treatment of insurgent youth, from adolescent fighters to very young children? Using an original survey, we examine public opinion regarding adolescent/child soldiers and young children in the Islamic State (ISIS) in Mosul, Iraq. Focusing retrospectively, we inquire about rehabilitative versus retributive preferences for minors who fought and worked for the Islamic State relative to adults. We find that retributive preferences toward minors are conditioned on their participation in violence, beliefs about the determinants of adulthood, and the role of agency versus coercion in the recruitment process. Looking prospectively, we find the public divided between fears over the threat posed by radicalized children within insurgency and hope for their rehabilitation and reintegration. Our results raise concerns about the detrimental effects of retributive justice and social stigma on the well-being of insurgent youth and children both now and later into adulthood.